Magnetotelluric response of anisotropic 2‐D structures - Osella, A.M. (1993)
b The effect of anisotropy on the distribution of Earth's conductivity is evaluated by calculating the electromagnetic response of multilayered 2‐D structures. The electric and magnetic fields are expanded in terms of Fourier series, the coefficients being obtained by applying the corresponding boundary conditions on each interface, given by arbitrary analytical functions. Then the results are used to analyse some particular structures. Copyright © 1993, Wiley Blackwell. All rights reserved